Modulation of Visceral Nociception, Inflammation and Gastric Mucosal Injury by Cinnarizine - Abdel-Salam, Omar M.E. (Libertas Academica, 2007)
The effect of cinnarizine, a drug used for the treatment of vertigo was assessed in animal models of visceral nociception, inflammation and gastric mucosal injury. Cinnarizine (1.25–20 mg/kg, s.c.) caused dose-dependent inhibition of the abdominal constrictions evoked by i.p. injection of acetic acid by 38.7–99.4%. This effect of cinnarizine (2.5 mg/kg) was unaffected by co-administration of the centrally acting dopamine D2 receptor antagonists, sulpiride, haloperidol or metoclopramide, the peripherally acting D2 receptor antagonist domperidone, but increased by the D2 receptor agonist bromocryptine and by the non-selective dopamine receptor antagonist chlorpromazine. The antinociception caused by cinnarizine was naloxone insenstive, but enhanced by propranolol, atropine and by yohimbine. The antinociceptive effect of cinnarizine was prevented by co-treatment with the adenosine receptor blocker theophylline or by the ATP-sensitive potassium channel (K(ATP)) blocker glibenclamide. Cinnarizine at 2.5 mg/kg reversed the baclofen-induced antinociception. Cinnarizine at 2.5 mg/kg reduced immobility time in the Porsolt’s forced-swimming test by 24%. Cinnarizine inhibited the paw oedema response to carrageenan and reduced gastric mucosal lesions caused by indomethacin in rats. It is suggested that cinnarizine exerts anti-inflammatory, antinociceptive and gastric protective properties. The mechanism by which cinnarizine modulates pain transmission is likely to involve adenosine receptors and K(ATP) channels.